Valid and practical integrated monitoring instrument of tahfidz qur'an - Efan, Efan; Saputra, Arie Yandi; Syahri, Riduan; Zulkipli, Zulkipli (SHM Publisher, 2024)
In implementing tahfidz qur'an learning in Islamic boarding schools, students must face many activities, and they are usually given up to five times a day. Almost all of these activities must be recorded by the teacher in a logbook so that there is the potential for slow and invalid reporting. This study aims to create an integrated monitoring instrument of tahfidz qur'an and reveal its validity and practical values. This study was conducted using a research and development (R&D) approach. The instrument was created by combining the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development procedure and the Rapid Application Development (RAD) development procedure. Furthermore, the application of the Object-Oriented Programming (OOP) paradigm into the application creation process aims to produce a monitoring instrument that is integrated into various types of devices and can provide data and information on the student's achievement of tahfidz qur'an learning to all interested parties. The results of the validity test revealed an Aiken's V value of 0.81 so it was worthy of being tested at the implementation stage. The implementation resulted in a practicality value of 80.65% from teachers, 79.84 from parents of students, and 78.28% from the management of the boarding school. Overall, both teachers, parents of students, and management stated that this integrated monitoring instrument of tahfidz qur'an was practical during use.